Diagnosis of tuberculosis in the context of occupational periodic evaluation: observactions to the current Peruvian regulations - Jhonston, Erik J. (2018)
Mr. Editor, in Peru, the current Occupational Health and Safety Law establishes that the employer is responsible for protecting the health of its workers through activities such as occupational medical examinations (EMO), which according to the Ministerial Resolution (RM) 312-2011 of the Ministry of Health (MINSA) are mandatory for each economic activity (1). Although this MRI has implied an advance in Peruvian occupational health, it has certain shortcomings with respect to tuberculosis screening, which could be preventing an accurate diagnosis in the vulnerable population.